A Byte Is All We Need. - Mitra, Ankita (Communications of the ACM, 2016)
The article discusses efforts to attract and engage women students in computer science, programming, and engineering curricula. Gender differences in boys' and girls' familiarity and aptitude with computers and computer programming are identified and the author emphasizes the alleged importance of exposure to video games in the stimulation of interest in computers.